Kebijakan Kesejahteraan Sosial bagi Migran yang Menikah dan Keluarganya di Republik Korea - Giwoong Son (Badan Strategi Kebijakan Hukum, 2025)
To ensure the safe settlement of marriage migrants and their families within the Republic of Korea's distinct multicultural context, it is essential to adopt both a rights-based and universal welfare approach to foster genuine inclusion. However, the current social welfare policy for marriage migrants and their families presents a social investment and labelling approach, revealing its difficulties and paradoxical impact toward their full inclusion. This study examines the social welfare policy for marriage migrants and their families, to identify and analyze the functional gaps and unintended consequences in existing welfare policies and advocate for a shift away from a labelling approach toward more inclusive and rights-based policies that support stable settlement. Through an extensive desk review of relevant research, legislation, government surveys, and policy audit reports concerning Korea's Multicultural Family Policy, this study presents recommendations for policy revision in response to the challenges embedded within the current framework. Rather than focusing solely on the expansion of services, the findings underscore the importance of enhancing service quality and implementation processes while addressing structural forms of discrimination. The study further advocates for a rights-based approach to welfare provision, moving away from selective, group-specific targeting and discretionary or charitable measures.